Analisis Faktor Konfirmasi Indeks Pembangunan Manusia Indonesia Tahun 2019-2020 - Hanifah, Nurul; Rachmawati, Rima (Fakultas Ekonomi Universitas Samudra, 2023)
The Human Development Index (IPM) is one of the development target indicators that is very important to pay attention to its development, because it is one of the main performance measurement indicators for Regional Incentive Funds (DID) in encouraging community welfare improvements. In 2020, Indonesia's HDI percentage slowed down by 0.03 percent. This research aims to examine the dimensions that need to be developed so that Indonesia's HDI achievements continue to increase. This descriptive and verification research uses a quantitative approach. Secondary data collected in this study were analyzed using confirmatory factor analysis. The results state that the dimension of a decent standard of living has the strongest contribution to HDI achievements. Another result is that Papua is a province with the lowest standard of living in Indonesia which is reflected in its per capita expenditure. Several factors contribute to the low standard of living in the province of Papua, namely the high unemployment rate and poverty rate.